Respuesta :
For this case we have the following system of equations:
[tex]y = -2x +3 y = -x + 1[/tex]
Equating the values of y we have:
[tex]-2x +3 = -x + 1 [/tex]
From here, we can clear the value of x.
We have then:
[tex]-2x + x = 1 - 3 -x = -2 x = 2[/tex]
Then, we look for the value of y.
For this, we substitute x in any of the equations:
[tex]y = -x + 1 y = -2 + 1 y = -1[/tex]
Answer:
The ordered pair solution of the system of equations, is given by:
[tex](x, y) = (2, -1)[/tex]
[tex]y = -2x +3 y = -x + 1[/tex]
Equating the values of y we have:
[tex]-2x +3 = -x + 1 [/tex]
From here, we can clear the value of x.
We have then:
[tex]-2x + x = 1 - 3 -x = -2 x = 2[/tex]
Then, we look for the value of y.
For this, we substitute x in any of the equations:
[tex]y = -x + 1 y = -2 + 1 y = -1[/tex]
Answer:
The ordered pair solution of the system of equations, is given by:
[tex](x, y) = (2, -1)[/tex]
Answer:
The two systems will intercept at point x = 2, y=-1
Step-by-step explanation:
The solution of the two equations can be determined using substitution:
[tex]y=-2*x+3[/tex] (1)
[tex]y=-x+1[/tex] (2)
Substitue equation 1 into 2:
We obtain the equation in terms of x and simplify
[tex]-2*x+3=-x+1[/tex]
[tex]x=2[/tex]
Therefore x=2 we can substitute into equation 2
[tex]y=-(2)+1= -1[/tex] (2)
Therefore the systems will intercept at point (2,-1)